The Impact and Prospect of China’s Low Interest Rates on the Economy - Fu Jiarui (SHS Web of Conferences)
This article explores the impact of China’s long-term low-interest-rate policy on its economy and its future development direction. While the low-interest-rate policy has stimulated investment and consumption, it has also led to risks such as rising asset prices, real estate market bubbles, and increasing debt levels. The squeeze on bank profit margins may affect the stability of the financial system. The article reviews the development of China’s interest rate policy since 1949, analyzes the impact of low interest rates on consumption and investment, and predicts the trend of future interest rate changes. The study shows that a decrease in deposit interest rates may reduce the willingness to save, and increase consumption and investment, but may also increase market volatility and investment risks. Changes in the global economic environment and the need for domestic economic structural adjustment make it particularly important to study the impact of low interest rates on China’s future economic development.